(3JfHjg Phi Gdgee Ydi eBNP Edi GdWjH ef GdTYQ hGdMces
(3ChdgG (B:s
(3Chd GdehLhO efg hQJHJ GdOjhGf Ydi MQha GdeYLe JQJjHkG de jSHbfi Zdjg ef JbOe s
(3BNQgG (B:s
(3hBNQ GdehLhO efg (B: (3heG cfJ eef COQc Gd MH HGdefi hdcf HGJGe GTJjf GdfhGUjG s
(3Cda gPG GdeNWhW dSja GdOjf Hf CHj fei Hf HQcGfs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs